Design and Implementation of Driver Assistance System using Machine Learning. Issue 1 (December 2020) - Bhargava, D. S.; Shyam, N.; Senthil Kumar, K.; Wasim Raja, M.; Sivashankar., P
Abstract: The main theme of the work is to detect the traffic sign boards and alert the driver accordingly, which helps in reducing the violation of the traffic rules and also reduces the accidents that occur in day-to-day life. The vehicle will be able to guide the driver by providing the details of speed limit, traffic sign boards in high pedestrian density areas and the driver can change the speed within which the vehicle needs to operate and drive safely. The components that are used in the system design are raspberry pi 3 (module-b), ultrasonic sensor and web camera. The images of the traffic sign boards are captured using a web camera and the speed limit of the vehicle can be changed accordingly by the driver and will not be allowed to exceed the speed limit. In addition this system may help in analyzing the driving pattern.